Techno-economic Evaluation of Stand-alone Hybrid Renewable Energy System for Remote Village Using HOMER-pro Software - Ajoya Kumar Pradhan; Mahendra Kumar Mohanty; Sanjeeb Kumar Kar (Institute of Advanced Engineering and Science, 2017)
The off-grid hybrid renewable energy generation system has lesser cost of energy with higher reliability when compared with solar Photovoltaic (PV) or wind energy system individually. The optimization design is worked out by reducing the Unit Cost Of Energy (UCOE) for different case studies and comparing the outcomes obtained by the use of HOMER-Pro (hybrid optimization model of electric renewable) software. The optimal cash flow analysis of hybrid energy system is based on the load patterns is discussed, solar irradiance (kW/m2) of site at proper latitude and longitude, wind speed and price of diesel, which is collected from a remote village in Khurda District, Odisha in India. Moreover, the optimization and sensitivity results of the system are find out by varying the input parameters like solar radiation, wind speed etc.